Genome-Wide Screening and Characterization of Methyl-CpG-Binding Domain (MBD) Proteins in Arabidopsis Species - Hong-Hui Cui; Man-Man Sun; Xiao-Juan Huang; Hong-Ze Liao (Current Issues in Molecular Biology)
Methyl-CpG-binding domain (MBD) proteins play vital roles in epigenetic gene regulation, and they have diverse molecular, cellular, and biological functions in plants. MBD proteins have been functionally characterized in a few plant species. However, the structure and function of MBD proteins in Arabidopsis halleri and Arabidopsis lyrata remain unknown. In this study, 12 A. halleri MBD (AhMBD) and 13 A. lyrata MBD (AlMBD) genes were identified. A phylogenetic analysis of the Arabidopsis genus showed that the MBD proteins of three species (Arabidopsis thaliana, A. helleri, and A. lyrata) could be classified into eight classes. Expression patterns suggested that the AtMBD genes were expressed in different tissues. We characterized the function of AtMBD3 and found that it was constitutively localized to the nucleus and interacted with several AtMBD protein members. Our results reveal that AtMBD3 is involved in the development of A. thaliana, which may be helpful in further studies on these genes in A. helleri and A. lyrata.